Urban trees of the Nilgiris district, Tamil Nadu, India - Jeevith, Selvaraj; Manjunath, Jahadesan (Biodiversity: Research and Conservation, 2023)
The study presents the current status of trees in urban landscapes of the Nilgiris district. In this study, 171 species belonging to 127 genera and 59 families were identified. The angiosperms were represented by 156 species and the gymnosperms by 15 species, identified as potential urban trees, including both wild and ornamental tree species. Among the 171 species, the Fabaceae were the dominant family (19 species), followed by the Myrtaceae (13 species) and Cupressaceae (6 species). Ornamentals accounted for 24% of all the species. A complete list of the recorded urban trees is provided, supplemented with their potential economic value.